2007
DOI: 10.2332/allergolint.o-06-473
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Leukotriene Receptor Antagonists in Preventing Common Cold-like Symptoms in Bronchial Asthma Patients

Abstract: Adult asthma patients undergoing treatment with LTRAs exhibit lower incidence rates of common cold-like symptoms than those not receiving LTRAs. LTRAs play an important role in reducing the incidence of common cold-like symptoms among asthma patients and in suppressing exacerbation of asthma symptoms possibly associated with these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…In agreement with the present study, LTRA treatment was associated with a lower incidence of common cold-like symptoms in a retrospective analysis of adult asthma. 21 However, contrary to the present results, Kozer et al reported that montelukast did not reduce the incidence or duration of URI in preschool-aged children who did not have asthma. 22 Thus, LTRA treatment may only be effective for asthmatic patients, who have higher LT levels in the airway while stable, to prevent URI symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with the present study, LTRA treatment was associated with a lower incidence of common cold-like symptoms in a retrospective analysis of adult asthma. 21 However, contrary to the present results, Kozer et al reported that montelukast did not reduce the incidence or duration of URI in preschool-aged children who did not have asthma. 22 Thus, LTRA treatment may only be effective for asthmatic patients, who have higher LT levels in the airway while stable, to prevent URI symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…LTs play a pivotal role in the acute phase of respiratory conditions such as (i) asthma, (ii) viral pneumonia, (iii) acute lung injury (ALI), (iv) systemic inflammatory response syndrome (SIRS), (v) ARDS, and (vi) pulmonary fibrosis (Beller et al, 2004;Caironi et al, 2005;Horiguchi et al, 2007;Okunishi and Peters-Golden, 2011;Al-Amran et al, 2013). LTs mediate various molecular and cellular pathologies in respiratory disease, and LT inhibition alleviates respiratory pathology (Sorkness, 1997;McMillan, 2001;Scott and Peters-Golden, 2013).…”
Section: Cysteinyl Leukotrienes In Lung and Respiratory Disease Pathomentioning
confidence: 99%
“…It has been reported that levels of sulfidopeptide leukotrienes are increased during infections with RSV, influenza, or HRV (Volovitz et al, 1988;Gentile et al, 2003), although data for the latter virus remain controversial. Several studies have reported that the use of leukotriene receptor antagonists, normally added on as a second-line treatment to usual ICS therapy, reduced asthma symptoms or exacerbations due to colds in children Horiguchi et al, 2007;Johnston et al, 2007;Robertson et al, 2007). By contrast, in children with RSV bronchiolitis, the use of montelukast did not reduce symptoms, nor did it significantly effect the number, or time to onset, of subsequent exacerbations (Bisgaard et al, 2008;Proesmans et al, 2009).…”
Section: Leukotriene Receptor Antagonists and Bronchodilatorsmentioning
confidence: 99%